Psychometric properties of the facial disability index in patients with facial palsy: A systematic review and meta-analysis - SARI, ZÜBEYİR (My University, 2022)
Purpose The aim of the study was to present the systematic review and meta-analysis of the psychometrical analysis of Facial Disability Index (FDI) studies. Methods A literature search was conducted in the relevant electronic databases “PubMed, Scopus, Web of Science (WoS), and Cochrane Library.” A total of 621 articles were obtained by searching the relevant keywords (PubMed: 384, Cochrane Library: 14, Web of Science: 132, Scopus: 91). A total of 8 papers were included. The four-point classifcation and ratingbased “COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN)” tools were used to evaluate the bias risk and evidence levels. Results Cronbach’s alpha pooling of FDI total score was (ES): 0.803 (95% CI: 0.73–0.86). Heterogeneity for the Facial Disability Index-Physical Function (FDI-PF) and Facial Disability Index-Social Function (FDI-SF) subscore based on intraclass correlation coefcient (ICC) were I 2=84.2% (ICC: 0.88, 95% CI: 0.81–0.92) and I 2=73.7% (ICC: 0.87, 95% CI: 0.81–0.90), respectively. Correlational results between Sunnybrook Facial Grading System (SFGS) with FDI-PF and FDI-SF were 0.38 and 0.22, respectively. The correlations of FDI-PF with Short Form-12 Physical Component Summary (SF-12-PCS) and Short Form-12 Mental Health Component Summary (SF-12-MCS) were 0.43 and 0.28, respectively. Correlation results of FDI-SF with SF-12-PCS and SF-12-MCS were 0.23 and 0.57. The relationship results of Facial Clinimetric Evaluation with FDI-PF and FDI-SF were 0.71 and 0.57, respectively. Conclusion FDI is a psychometrically valuable questionnaire, especially for the internal consistency, reliability, and validity. In clinical practice, the use of FDI would be valuable, in addition to clinician-based grading, to see more of patients’ social infuences precisely.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; Life Sciences; Natural Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Developmental Neuroscience; Cellular and Molecular Neuroscience; Cognitive Neuroscience; General Neuroscience; Neuroscience (miscellaneous); Sensory Systems; Human-Computer Interaction; Neurology (clinical); Physical Sciences; Bell's palsy; Facial disability; FDI, reliability; Responsiveness; Validity; QUALITY-OF-LIFE; RELIABILITY; VALIDATION; RECOVERY; CRITERIA; VERSION; NERVE; MOTOR; FDI; Bell’s palsy; Bell’s palsy; Facial disability; FDI; reliability; Responsiveness; Validity